Wage and price dynamics in a large emerging economy: The case of China - Carsten A. Holz; Aaron Mehrotra (Bank of Finland, Institute for Economies in Transition (BOFIT), 2014)
This study finds that the growth in labour costs in China is not passed through fully to final prices in China, neither in the tradable goods sector nor in the economy as a whole. This probably reflects the strong pressure on profit margins from a highly competitive environment, especially in manufactured goods. The potential implications of labour cost increases in China for global inflation pressures are also discussed.
URN:NBN:fi:bof-201408072219
Keywords: E31; F42; J30; 330; labour costs; inflation; China; global economic slack; globalization